Effect of a Probiotic Combination in an Experimental Mouse Model and Clinical Patients With Chronic Kidney Disease: A Pilot Study - Wang, I-Kuan; Yen, Tzung-Hai; Hsieh, Pei-Shan; Ho, Hsieh-Hsun; Kuo, Yi-Wei; Huang, Yen-Yu; Kuo, Yu-Lun; Li, Chi-Yuan; Lin, Hung-Chih; Wang, Jiu-Yao (Frontiers in Nutrition, 2021)
The aim of the present study is to evaluate whether probiotics could delay the decline of renal function. C57BL/6 mice (6–8 weeks of age, male) were fed with adenine to induce chronic kidney disease (CKD). The experimental groups were additionally supplemented with 109 colony-forming units (CFU)/day (high-dose) and 107 CFU/day (low-dose) probiotics containing Lactobacillus acidophilus (TYCA06), Bifidobacterium longum subspecies infantis (BLI-02), and Bifidobacterium bifidum (VDD088), respectively. Renal function and histology were examined. The stage 3 to 5 CKD patients not on dialysis were recruited from July 2017 to January 2019. Two capsules of probiotics containing 2.5x109 CFU with the same composition were administered twice daily for 6 months. The decline rate of estimated glomerular filtration rate (eGFR) was measured before and after intervention. In addition, changes in the serum endotoxin and cytokine levels, scores of gastrointestinal symptoms, and stool microbiota were measured. Probiotics could attenuate renal fibrosis and improve renal function in CKD mice. Thirty-eight patients completed the 6-month study. The mean baseline eGFR was 30.16 ± 16.52 ml/min/1.73 m2. The eGFR decline rate was significantly retarded from -0.54 (-0.18, -0.91) to 0.00 (0.48, -0.36) ml/min/1.73 m2/month (p < 0.01) after 6-month treatment. The serum levels of TNF-α, IL-6, IL-18, and endotoxin were significantly decreased after treatment. The scores of borborygmus and flatulence and the stool forms significantly improved. The abundance of Bifidobacterium bifidum and Bifidobacterium breve in stool microbiota increased significantly. In conclusion, probiotics might attenuate renal function deterioration in CKD mice and patients.